Disparities in Loss from COVID-19: Comparing across and among First- and Second-Generation Latinx and Asian Adults. (April 2022) - Moinester, Margot; Schachter, Ariela; Siegrist, Ella
The coronavirus disease 2019 (COVID-19) pandemic has resulted in more than 900, 000 deaths in the United States, disproportionately affecting racial and ethnic minorities. The pandemic is likely leading to disparate experiences of loss, though little research to date has examined disparities in experiences of loss from COVID-19. Drawing on a nationally representative survey of 6, 000 first- and second-generation Latinx and Asian adults carried out in April and May 2021, this study reveals sharp disparities between and within ethnoracial groups in the United States in the experience of losing household members or close family and friends to COVID-19. Latinx adults were 1.65 times more likely than Asian adults to experience the loss of a loved one from COVID-19 (38 percent vs. 23 percent). First- and second-generation Indian Americans experienced disproportionately high rates of loss relative to other Asian Americans (33 percent). Looking both across and within ethnoracial categories is critical for understanding how the pandemic has compounded preexisting disadvantage.